Financing Agricultural Development: The Political Economy of Public Spending on Agriculture in Sub-Saharan Africa - Regina Birner; Nethra Palaniswamy (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
Acknowledging that the agricultural sector can play an important role as an engine of pro-poor growth in Sub-Saharan Africa, the purpose of this paper is to identify the factors that influence the 'political will' of governments to support this sector. The concept of 'political resources' from the political science literature is used to guide the analysis, as it combines the insights from state-centered and society-centered approaches to explain agricultural policies. Drawing on panel data covering 14 Sub-Saharan African countries over the period 1980-2001, we present empirical evidence showing that political factors play an important role in determining government's commitment to supporting agricultural development. We use a measure of democracy that varies both across countries and within countries over time. Estimates are presented for separate samples of democracies and non-democracies, and for a pooled sample of all countries and years irrespective of the democratic status. Our results suggest that the rural poor do exercise electoral leverage in democracies; larger rural population shares are associated with higher spending on agriculture in democracies but not in authoritarian regimes. We also find evidence consistent with the theoretical prior that larger farmers tend to be better organized in interest groups. Specifically, we find that the share of traditional agricultural exports such as coffee and cocoa in the total value of exports, which may be an indicator for the ability of farmers' to organize themselves as interest groups, induces greater spending on agriculture. This result holds true for both democracies and nondemocracies.
Keywords: H3; O13; H5; Q18; 330